Reconstruction of Historical Literature of Bugis-Makassar (Stemma Model Philological Studies) - Kasma F Amin; Muliadi Muliadi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research was conducted to reconstruct literary works that contain the history of the life journey of the Makassar Bugis people in South Sulawesi. Information about the history of the journey of the Bugis Makassar community through literary works is interesting to reconstruct as an effort to understand the various facts of the life of the Bugis Makassar community. The problem discussed in this paper is what is the form of reconstruction of Bugis Makassar historical literature? The aim to be achieved is to find the results of the reconstruction of Bugis-Makassar historical literature. The method used is descriptive qualitative with a stemma model philological study approach. The results of data analysis show the results of the reconstruction of Bugis-Makassar historical literature which has six stages of events that mark the development and phases of the life of the Bugis Makassar community. Each period is marked by the works and literary figures of its era. The first period is the structuring of social life, the second period is the sianrebale era / the era of destruction, the third period is the era of resurrection, the fourth period is the golden age of the kingdom, the fifth period is the Dutch colonial era, and the sixth period is the era of independence. Every period there are phenomenal works that mark the times and historical figures who became legends in the Bugis Makassar community. The life phase of the Bugis Makassar community contained in historical literary works can be an important lesson in dealing with various phenomena of a better social life.